Service Integration as a Strategic Capability: Examining Its Impact on Customer Satisfaction in B2B Logistics - Ely Yanty; Timotius FCW Sutrisno; Liliana Dewi (SAFE-Network, 2026)
The increasing complexity of supply chain operations driven by digitalization and global trade has intensified the need for integrated logistics solutions, particularly in Business-to-Business (B2B) contexts. This study examines the role of one-stop integrated logistics services in influencing customer satisfaction based on the Resource-Based View (RBV). A quantitative approach was used by collecting survey data from 100 B2B customers of integrated logistics providers in Indonesia and analyzing them using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that service integration positively and significantly affects customer satisfaction, both directly and indirectly through logistics service quality. Integration capability also improves logistics service quality and perceived value. However, only logistics service quality significantly influences customer satisfaction, while perceived value has no significant effect. Customer trust is also identified as a strong predictor of satisfaction, although its moderating role is unsupported. These results indicate that customer satisfaction in B2B logistics is mainly driven by operational reliability and trust rather than value considerations. Managerially, companies should strengthen service integration, operational performance, and customer trust to enhance satisfaction and long-term relationships.